2017
DOI: 10.1515/jso-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Causal Social Construction

Abstract: Social constructionist claims are surprising and interesting when they entail that presumably natural kinds are in fact socially constructed. The claims are interesting because of their theoretical and political importance. Authors like Díaz-León argue that constitutive social construction is more relevant for achieving social justice than causal social construction. This paper challenges this claim. Assuming there are socially salient groups that are discriminated against, the paper presents a dilemma: if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Objektivitas baru bisa terjadi melalui penegasan berulang-ulang yang diberikan oleh orang lain yang memiliki definisi subyektif yang sama. Pada tingkat generalitas yang paling tinggi, manusia menciptakan dunia dalam makna simbolis yang universal, yaitu pandangan hidupnya yang menyeluruh, yang memberi legitimasi dan mengatur bentuk-bentuk sosial serta memberi makna pada berbagai bidang kehidupannya (Marques, 2017).…”
Section: Pembahasan Eksistensi Ppai Ketapang Dalam Presfektif Teori Kunclassified
“…Objektivitas baru bisa terjadi melalui penegasan berulang-ulang yang diberikan oleh orang lain yang memiliki definisi subyektif yang sama. Pada tingkat generalitas yang paling tinggi, manusia menciptakan dunia dalam makna simbolis yang universal, yaitu pandangan hidupnya yang menyeluruh, yang memberi legitimasi dan mengatur bentuk-bentuk sosial serta memberi makna pada berbagai bidang kehidupannya (Marques, 2017).…”
Section: Pembahasan Eksistensi Ppai Ketapang Dalam Presfektif Teori Kunclassified
“…Haslanger (2012, p. 183-184) writes that "the goal of social constructionist analyses is to locate the (often obscure) mechanisms of injustice and the levers for social change". Marques (2017) stresses that it is indispensable for a constructionist agenda to identify the mechanisms by which social factors contribute to X, and continues by giving concrete examples of the mechanisms by which stereotypes and silencing produce gender-related facts. Mallon's (2016) account of the construction of causally relevant social roles comprises a detailed clarification of the mechanisms by which various social factors contribute to bringing about and sustaining causally salient human categories.…”
Section: Causation As Production and Causation As Difference-makingmentioning
confidence: 99%
“…Thus, having revealed that social factors SF constitute X, one has automatically demonstrated that replacing SF with some alternative social factors SF* results in X ceasing to be the case. Marques (2017) has offered some pertinent reasons why Diaz-Leon is wrong to dismiss the relevance of causal construction for project (B).…”
Section: Causal Construction and Contrastive Causationmentioning
confidence: 99%
“…In a nutshell, nominal definitions are generally taken to specify the meaning of a term, while real definitions are generally taken to specify the essence of the thing to which that term refers(Rosen 2015).11 Note here that I am not claiming that these patterns of behavior are the only things in the real definition of C.12 Note that language might play a causally constructing role in addition to a constitutively constructing role here. For example, TeresaMarques (2017) has recently argued that we would do well to work with both causal construction and…”
mentioning
confidence: 99%